Contributions to the humoral immunological profile in broiler chickens treated with 50% Amoxidem - Turcu, D.,; Mariana Oporanu,; Condur, D.,; Grigorescu, P.,; Roman, M. (Medicamentul Veterinar)
Investigation on the effect of Amoxidem 50% humoral immunological effectors (protein fractions, lysozyme, total protein) in broilers was conducted. There were two groups of chickens tested: control group A and group B treated with Amoxidem 50%. Blood sampling was performed 7 days after treatment. Electrophoretic pattern of serum protein fractions in the experimental group showed a significant increase in the concentration of globulin fractions α1, α2 globulin and γ globulin and a decrease in the A/G ratio. Mean IgG level increased significantly (p˂0.001) in group B compared to group A. The serum’s lysozyme concentration showed a significant increase in statistical terms (p˂0.01) in group B compared with group A.